Study of autoclaved aerated concrete masonry walls under vented gas explosions. (15th June 2017) - Li, Zhan; Chen, Li; Fang, Qin; Hao, Hong; Zhang, Yadong; Chen, Wensu; Xiang, Hengbo; Bao, Qi
Highlights: Field test of unreinforced autoclaved aerated concrete masonry walls against vented gas explosions was conducted. Numerical model of masonry walls under gas explosions was calibrated with test data. Parametric studies of masonry walls were carried out with the calibrated model. Predictions of equivalent SDOF methods from public studies were compared and discussed. Abstract: A total of nine full-scale in-situ tests were carried out to investigate the performances of autoclaved aerated concrete (AAC) masonry walls subjected to vented gas explosions. The testing data including overpressure time histories of vented gas explosions, displacement time histories, and damage characteristics of AAC masonry walls in each test were recorded and analysed. It was found that the responses of masonry walls mainly depend on the peak value of overpressure and couple with the time history of gas explosion loads. Typical one-way or two-way flexural mode dominates the failure of AAC walls under vented gas explosions. A detailed micro model for masonry walls was developed in LS-DYNA, incorporating material parameters that were obtained from material tests. The accuracy of numerical model in predicting the responses of masonry walls was verified with the testing data. Parametric studies were conducted to explore the influences of block strength, boundary condition and wall thickness on the performances of masonry walls. The results reveal both wall thickness and boundary condition have significant influences on the response of the masonry wall while block strength has limited effect on its performance. The testing data were compared with the analytical predictions by using design code UFC 3-340-2 and equivalent single-degree-of-freedom (SDOF) methods developed respectively by Biggs and Morison. The results indicate that these predictions on one-way specimens agree well with the testing data, while the performance of two-way specimens is overestimated by using these three methods.